Determinants of neonatal vitamin D levels as measured on neonatal dried blood spot samples - Smith, C; Sun, C; Pezic, A; Rodda, C; Cameron, F; Allen, K; Craig, M; Carlin, J; Dwyer, T; Lucas, R; Eyles, D; Kemp, A; et al. (Karger Publishers, 2016)
BACKGROUND: Vitamin D deficiency is linked to adverse childhood health outcomes, yet data on the distribution and quantifiable determinants of neonatal 25-hydroxyvitamin D3 (25OHD) concentration, a vitamin D biomarker, are limited. OBJECTIVE: Our aim was to identify determinants of neonatal 25OHD concentration, measured using neonatal dried blood spots (DBS). METHODS: A total of 259 ethnically diverse children aged 0-16 years born in Victoria, Australia, were recruited. Data included maternal sun exposure, skin type, 25OHD concentration on stored neonatal DBS, and genotypes at the target genes. Associations were investigated using multiple linear regression models. RESULTS: The median 25OHD concentration was 29.2 nmol/l (IQR 18.0-47.4). Measured 25OHD was <50 nmol/l in almost half of the neonatal sample. Ambient ultraviolet radiation (UVR) 6 weeks before birth was the strongest predictor of neonatal 25OHD, accounting for 23% of its variation. A further 10% was explained by infant genetic variants at GC (rs2282679), the gene encoding the vitamin D binding protein, and DHCR7 (rs12785878), a gene required for synthesis of 7-dehydrocholesterol, a precursor to 25OHD. DBS age explained 7%, and patterns of maternal sun exposure and clothing choices accounted for 4%. A child's skin colour was strongly associated with GC gene variants and not independent of these variants in predicting 25OHD. The final model explained 43% of the total variance in neonatal 25OHD concentration. CONCLUSION: Maternal lifestyle factors and infant genetic variants predict neonatal 25OHD levels; the importance of maternal UVR exposure in late pregnancy is highlighted.